Friendship Networks and Political Opinions: A Natural Experiment among Future French Politicians - Yann Algan; Nicolò Dalvit; Quoc-Anh Do; Alexis Le Chapelain; Yves Zenou (Center for Economic Studies and ifo Institute (CESifo), 2023)
We study how social interaction and friendship shape students' political opinions in a natural experiment at Sciences Po, the cradle of top French politicians. Quasi-random assignments of students into the same short-term integration groups before their scholar curriculum reduce political opinion gap, and increase friendship formation. Using the pairwise indicator of same-group membership as instrumental variable for friendship, we find that friendship causes a reduction of differences in opinions by 40% of the standard deviation of opinion gap. The evidence is consistent with a homophily-enforced mechanism, by which friendship causes initially politically-similar students to join political associations together, which reinforces their political similarity, without exercising an effect on initially politically-dissimilar pairs. Friendship affects opinion gaps by reducing divergence, therefore polarization and extremism, without forcing individuals' views to converge. Network characteristics also matter to the friendship effect.
Keywords: C93; D72; Z13; 330; political opinion; social networks; friendship effect; polarization; homophily; extremism; natural experiment